Factors responsible for turnover in a fast food company of Santa Maria – RS - Rosa, Marian dos Santos; Ibdaiwi, Thiago Kader (Revista de Administração da UFSM, 2012)
In the current scene of the organizations, each time more, the collaborator comes conquering excellent space, where the good course of the functional activities depends on the motivation of each one of these members. Inside of this context, the present objective study to analyze the organizational climate, focusing in the motivation and the rotation of the collaborators of a great company of Fast Food of the city of Saint Maria- RS, known world-wide in this sort. Study of cases was carried through, using the Survey method, being the characterized research as exploratory, quantitative and descriptive, where 57 collaborators had answered to a questionnaire of 65 questions having aimed at to answer the problematic one of the study. The gotten results disclose that the collaborators correctly are trained and as consequence the quality is seen as a positive factor, however one has left of these collaborators if it showed not motivated, influenced for the half organizational not to be very healthful, had to the environment of extreme pressure that is part of the routine of this organization, beyond a sufficiently young team of collaborators, main factors of an index of turnover considerable, identified in this company.